The toxic effects of yeast Ppz1 phosphatase are counteracted by subcellular relocalization mediated by its regulatory subunit Hal3. Issue 12 (23rd March 2022) - Albacar, Marcel; Velázquez, Diego; Casamayor, Antonio; Ariño, Joaquín
Abstract : Overexpression of Saccharomyces cerevisiae protein phosphatase Ppz1 strongly impairs cell growth. Ppz1 is negatively regulated by its subunit Hal3, and Hal3 overexpression fully counteracts the toxic effects derived from high levels of the phosphatase. We show that Ppz1 localizes at the plasma membrane, and that co‐expression of Hal3 recruits Ppz1 to internal membranes (mostly vacuolar). This effect is not observed in a catalytically impaired mutant of Ppz1. Disruption of intracellular trafficking by deletion of the ESCRT‐0 component VPS27 abolishes both Hal3‐mediated relocalization of Ppz1 and normalization of cell growth, without affecting Ppz1 protein levels. We propose that Hal3 counteracts the toxic effects caused by excess of Ppz1 not only by inhibiting its enzymatic activity but also by recruiting the phosphatase to internal structures. Abstract : High levels of the yeast Ppz1 phosphatase are toxic, and expression of its inhibitory subunit Hal3 restores normal growth. We demonstrate that, besides inhibiting the phosphatase enzymatic activity, Hal3 relocalizes Ppz1 from its normal plasma membrane location to intracellular membranes (mostly vacuolar). This relocalization event is crucial for counteraction of the toxic effects of Ppz1, revealing an unsuspected regulatory mechanism of the phosphatase.